Addressing renewable energy investments with a strategic perspective - Karakeçe, Ercan (Emerald Group Publishing Ltd., 2023)
This chapter will focus on renewable energy investments in sustainable business projects from a strategic management and entrepreneurial perspective. It will be questioned what the concept of energy is/should be from the perspective of managers and entrepreneurs. For this purpose, it will start with the significance of energy for these two viewpoints and persist in its linkage with the requirements of energy acquisitions. The subject of energy and energy investments will be associated with concepts such as sustainability, interaction with environmental factors, and competitiveness. To address these concerns, SWOT analysis, resource dependence model, Porter's five forces analysis, the environmental Kuznets curves hypothesis, and strategy tripod perspective-therefore, resource, industry, and institutional-based approaches-will be examined and interpreted with energy and energy investments. In addition, soft issues related to energy will be discussed from the perspective of the entrepreneur, and it will be emphasized that energy and energy investments should be addressed more comprehensively. As a result of all these efforts, it is aimed to contribute to a more stable system for a sustainable and competitive energy policy.
Keywords: Energy; Energy Economics; Energy Investments; Entrepreneurial Perspective; Financial Innovation; Green Energy; Managerial Perspective; Renewable Energy; Strategic View; Sustainability